Diabetic Muscle Infarction: A Rare Cause of Acute Limb Pain in Dialysis Patients - G. De Vlieger; B. Bammens; F. Claus; R. Vos; K. Claes (Case Reports in Nephrology)
Diabetic muscle infarction is a rare microangiopathic complication occurring in patients with advanced diabetes mellitus. Diabetic patients with chronic kidney disease stage Vd are prone to develop this complication. The presenting symptom is a localized painful swelling of the affected limb. Symptoms usually resolve spontaneously during the following weeks, but frequent relapse can occur and in some cases swelling may lead to compartment syndrome. Biochemical blood analyses show an elevated C-reactive protein, but creatine kinase is often normal. Diagnosis can be made on clinical presentation and imaging, with magnetic resonance imaging as the gold standard. Histology is often not contributive. Treatment consists of rest, analgesics, rigorous glycemic control and low-dose aspirin. Severe cases of compartment syndrome require fasciotomy. In the current paper, we present two diabetic patients with cystic fibrosis, who are treated with automated peritoneal dialysis and suffered from episodic lower limb infarction. We subsequently review 48 episodes of diabetic muscle infarction previously reported in the literature in patients with end-stage renal disease.